2016
DOI: 10.2527/jas.2016-0673
|View full text |Cite
|
Sign up to set email alerts
|

Altering the time of vaccination against respiratory pathogens to enhance antibody response and performance of feeder cattle1

Abstract: Ninety Angus × Hereford calves were ranked by sex, BW, and age and assigned to 1 of 3 vaccination schemes against the bovine respiratory disease complex: 1) vaccination at weaning (d 0) and a booster at feedlot entry (d 30; CON; = 30), 2) vaccination 15 d before weaning (d -15) and a booster 15 d before feedlot entry (d 15; EARLY; = 30), and 3) vaccination 15 d after weaning (d 15) and a booster 15 d after feedlot entry (d 45; DELAYED; = 30). From d -15 to 7, calves were maintained as a single group on pasture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…*P ≤ 0.05. Lippolis et al, 2016). In the current study, pre-weaning vaccination decreased pre-weaning calf ADG by 41% compared with calves assigned to post-weaning vaccination, whereas post-weaning vaccination decreased calf ADG from d 7 to 21 (first 14 d after first round of vaccination) by 28% compared with calves that received pre-weaning vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P ≤ 0.05. Lippolis et al, 2016). In the current study, pre-weaning vaccination decreased pre-weaning calf ADG by 41% compared with calves assigned to post-weaning vaccination, whereas post-weaning vaccination decreased calf ADG from d 7 to 21 (first 14 d after first round of vaccination) by 28% compared with calves that received pre-weaning vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine-induced neutralizing antibody titers provide an indication of immune protection (Bolin and Ridpath, 1990) and vaccine efficacy in calves (Callan, 2001;Richeson et al, 2008). The ability of an animal to respond to vaccination varies from animal to animal and depends on environmental and genetic factors, maternal antibody concentrations (Downey et al, 2013), stress and previous exposure to pathogens (Loerch and Fluharty, 1999), frequency of energy supplementation (Artioli et al, 2015;Silva et al, 2017), metabolizable protein supply (Moriel et al, 2015), maternal energy-restriction during late gestation (Moriel et al, 2016b), and timing of vaccination (Richeson et al, 2008;Lippolis et al, 2016). However, it is still poorly understood how acquired antibody levels may be affected by the timing of vaccination associated with other stressful calf management practices.…”
Section: Itemmentioning
confidence: 99%
“…Research into response to vaccination has identified multiple environmental and management variables which impact an individual calf’s ability to mount an antibody response [79]. Factors such as maternally derived antibody levels from colostrum, calf age, seasonality, and weaning status all impact a calf’s individual immune system, and result in variability in its response to vaccination [1012].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of BRD cases occur within the first 14 d upon feedlot entry (Kirkpatrick et al, 2008), and delaying vaccination may not provide full immunological protection to newly received cattle. In turn, Lippolis et al (2016) reported that advancing the time of BRD vaccination, by providing the first dose prior to weaning and revaccination during a 30-d preconditioning program, enhanced cattle performance and antibody response to bovine viral diarrhea viruses (BVDV) and Mannheimia haemolytica (MH) during feedlot receiving. Nevertheless, these authors failed to report substantial treatment impacts on BRD incidence, given that morbidity rates were not as prevalent when compared to commercial feedlots (Snowder et al, 2006;Marques et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these authors failed to report substantial treatment impacts on BRD incidence, given that morbidity rates were not as prevalent when compared to commercial feedlots (Snowder et al, 2006;Marques et al, 2016). Lippolis et al (2016) concluded that additional research was warranted to validate their results in high-stress feedlot environments, including evaluation of a greater number of animals, antibody response to vaccination against other BRD viruses, and cattle performance until slaughter. Based on this rationale, we hypothesized that advancing the time of vaccination against BRD pathogens, by providing both doses prior to feedlot entry, mitigates BRD incidence and promotes performance of cattle in a commercial feedlot system.…”
Section: Introductionmentioning
confidence: 99%